Isoschaftoside Inhibits Lipopolysaccharide-Induced Inflammation in Microglia through Regulation of HIF-1α-Mediated Metabolic Reprogramming. (23rd November 2022) - Guan, Shuyuan; Sun, Lingbin; Wang, Xihua; Huang, Xirui; Luo, Tao
Abstract : Isoschaftoside is a C-glycosyl flavonoid extracted from the root exudates of Desmodium uncinatum and Abrus cantoniensis . Previous studies suggested that C-glycosyl flavonoid has neuroprotective effects with the property of reducing oxidative stress and inflammatory markers. Microglia are key cellular mediators of neuroinflammation in the central nervous system. The aim of this study was to investigate the effect of isoschaftoside on lipopolysaccharide-induced activation of BV-2 microglial cells. The BV-2 cells were exposed to 10 ng/ml lipopolysaccharide and isoschaftoside (0–1000  μ M). Isoschaftoside effectively inhibited lipopolysaccharide-induced nitric oxide production and proinflammatory cytokines including iNOS, TNF- α, IL-1 β, and COX2 expression. Isoschaftoside also significantly reduced lipopolysaccharide-induced HIF-1 α, HK2, and PFKFB3 protein expression. Induction of HIF-1 α accumulation by CoCl2 was inhibited by isoschaftoside, while the HIF-1 α specific inhibitor Kc7f2 mitigated the metabolic reprogramming and anti-inflammatory effect of isoschaftoside. Furthermore, isoschaftoside attenuated lipopolysaccharide-induced phosphorylation of ERK1/2 and mTOR. These results suggest that isoschaftoside can suppress inflammatory responses in lipopolysaccharide-activated microglia, and the mechanism was partly due to inhibition of the HIF-1 α -mediated metabolic reprogramming pathway.